The future of arms control - Levi, Michael A.; O'Hanlon, Michael E.; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2005)
"Lays out the framework of an enduring and effective arms control strategy that is explicitly linked to broader U.S. security policy, focusing on preventing the spread of nuclear and biological arms to extremist states and terrorist organizations"--Provided by publisher.
Introduction and rationale -- Traditional strategic arms control -- Preventing nuclear proliferation -- Controlling the new technologies -- Compelling compliance -- Conventional arms control and regional conflict -- The future of arms control.
Includes bibliographical references (p. 165-184) and index.
Electronic reproduction.
Keywords: Arms control -- United States; International relations; Security, International; Nuclear disarmament; United States -- Foreign relations; Electronic books